New insights on the relative contributions of coastal processes and tectonics to shore platform development following the Kaikōura earthquake. Issue 13 (15th June 2017) - Stephenson, Wayne J.; Dickson, Mark E.; Denys, Paul H.
Abstract: We describe the immediate impact of the 14 November 2016 Kaikōura magnitude 7.8 (Mw) earthquake on shore platforms and cliffs around Kaikōura Peninsula. The earthquake caused an instantaneous uplift of 1.01 m of the peninsula. We resurveyed seven profiles previously used for erosion monitoring and observed changes in the configuration of the shoreline. The coseismic uplift has fundamentally changed the process regime operating on the platforms and altered the future trajectory of shore platform and cliff development. Our observations highlight the interplay of waves, weathering, biology and tectonics. At this location tectonism strongly modulates the process regime, driving instantaneous changes in morphology and altering rates and patterns of erosion. Finally, the uplift of the Kaikōura coast has implications for changing resilience to climate change and sea level rise. Copyright © 2017 John Wiley & Sons, Ltd.